2008
DOI: 10.1016/j.orgel.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Integrating organic light-emitting diode and field-effect-transistor in a single device

Abstract: We have investigated organic light-emitting diodes (OLEDs) with a structure of field-effect-transistor (FET) using MgAg as source and drain electrode, respectively. These devices were found to present both a typical switchable behavior of FET and an electro-optical transfer characteristic of OLEDs. Five organic layers were employed in devices that were expected to play each role for OFET and OLED, respectively. In a result, the FET unipolar behavior has been demonstrated experimentally. Furthermore, FET charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Wei et al constructed an OLED in the OFET architecture. But the organic layer in the transistor consists of all of the components required for both the OLED and OFET.…”
Section: Developments In the Device Architecturementioning
confidence: 99%
“…Wei et al constructed an OLED in the OFET architecture. But the organic layer in the transistor consists of all of the components required for both the OLED and OFET.…”
Section: Developments In the Device Architecturementioning
confidence: 99%
“…Metallized plastics are widely used in products [2] ranging from car reflectors, compact discs and electric shielding to foils for food packing and biosensors. The polymer/metal structures form a base for construction of light emitting diodes in optoelectronics [3]. The creation of metallic ad-layers is governed by complex nucleation processes, which are still not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The crucial reasons are low charge capacity of gate insulator and large gate leakage current caused by defects states in the organic dielectric. [1][2][3][4][5] To complete the requirements of low voltage operation, several methods have been proposed to enhance the capacitance of gate dielectric and reduce the leakage current of OTFTs. In 2004, Halik et al demonstrated low-voltage organic transistors by using amorphous molecular self-assembled monolayer (SAM) gate dielectric.…”
Section: Introductionmentioning
confidence: 99%